Salmonella Typhimurium Level in Mealworms (Tenebrio molitor) After Exposure to Contaminated Substrate - Jensen, Annette Nygaard; Hansen, Sussie Hjort; Baggesen, Dorte Lau (Frontiers in Microbiology, 2020)
Findings of viable Salmonella spp., which are important foodborne pathogens, are seemingly not reported in mealworms (Tenebrio molitor) for feed and food. Still, the bacterial load of mealworms is naturally high and includes members of the Enterobacteriaceae family to which Salmonella belong. This indicates that Salmonella may be able to thrive in mealworms if introduced into the production. Therefore, this study aimed to assess the quantitative level of Salmonella enterica serovar Typhimurium (ST) in mealworm larvae over a 14-day course after exposure to substrate contaminated with ST levels from 1.7 to 7.4 log CFU/g at start (i.e. day 0). The level of ST found in larvae were below the quantitative detection level (1 or 2 log CFU/g) on day 1 in larvae exposed to contamination levels of 1.7, 3.4 and 3.6 log CFU/g opposed to contamination levels of 5.4, 5.6 and 7.4 log CFU/g, respectively. The maximum level of ST detected in individual 1-g larvae samples was 5.8 log CFU/g, but the level varied among the triplicate samples from each sampling, and the highest average value was 5.3±0.3. Beyond day 7, only larvae exposed to the contamination level of 7.4 log CFU/g were >1.0 log CFU/g in the triplicate samples. However, qualitative testing (10 g) showed the presence of ST in larvae until the end of the experiment at day 14 except for the lowest contamination level of 1.7 log CFU/g. Parallel testing of surface disinfected larvae indicated that some larvae may be ST-positive due to Salmonella residing on the surface only. Still, any detection of Salmonella is of concern from a food safety perspective. In substrate with contamination levels below 3.6 log CFU/g, the level of ST was below the quantitative detection limit within a few days. Still, ST was detected until the end of experiment at day 14 except for the lowest contamination level of 1.7 log CFU/g. This study indicates the importance of avoiding introduction of Salmonella into the production e.g. via contaminated substrate in order to avoid Salmonella-positive larvae as they remained positive for at least 14 days (except at the lowest contamination level).